Problemi interpretacje i prevođenja stare književnosti. Nekoliko pitanja, primjedbi i propozicija / Problemy interpretacji i tłumaczenia literatury dawnej. Kilka pytań, uwag i propozycji - Milanović, Zvonimir (Przekłady Literatur Słowiańskich, 2016)
The Problems of Interpreting and Translating Old Literature. Several questions, comments and propositions In this paper I have analyzed some translatological questions in the field of translating old literature, on the basis of selected fragments from the works of Jan Kochanowski and from the essay of Czesław Miłosz that examines some translatological problems. An analysis of the cited fragments and their translations shows that the translation of Renaissance literature should also opt for knowledge of contemporary poetics and rhetorical rules, which formed a part of the legacy from the literature of the ancient period. In addition, as Miłosz postulates in his essay, it seems that in the process of a translation of great significance is the empathy of the translator himself with the persona of a given author. Literary interpretation and the correct understanding of old literature is a crucial factor and the starting point in the translation process. Such an interpretation is based on a thorough knowledge of the epoch and the culture of the Renaissance period, within which the concrete work was written. Key words: translation studies, translation, interpretation, Kochanowski, old literature